A de novo Variant of ASXL1 Is Associated With an Atypical Phenotype of Bohring-Opitz Syndrome: Case Report and Literature Review - Zhao, Weiqing; Hu, Xiao; Liu, Ye; Wang, Xike; Chen, Yun; Wang, Yangyang; Zhou, Hao (Frontiers in Pediatrics, 2021)
Bohring-Opitz syndrome (BOS) is a rare genetic disease first reported by Bohring et al. in 1999. With the recent development of exome sequencing (ES), de novo truncating mutations in the additional sex-combs-like 1 (ASXL1) gene have been causally implicated in BOS. Herein, we describe a 7-month-old girl with intrauterine growth restriction, severe pulmonary infection, seizures, and craniofacial abnormalities (microcephaly, micro/retrognathia, hypertelorism, depressed nasal bridge, low-set ears and hypertrichosis) at birth. At a later stage, the patient developed global developmental delay. We performed ES and identified a de novo heterozygous mutation in ASXL1, namely, c.1210C>T/p.R404*. However, this case did not have trigonocephaly, facial hemangioma, prominent eyes, myopia, BOS posture, or brain abnormalities (enlarged subarachnoid spaces, agenesis of the corpus callosum, moderately enlarged cerebral ventricles, or prominent frontal subarachnoid spaces), which are common characteristics in most patients with BOS-harboring ASXL1 mutations. These new data expand the phenotype of BOS driven by ASXL1 and may assist in more accurately delineating the phenotypes caused by variants of this gene.